تطبيق متطلبات إدارة الجودة الشاملة البيئية ودورها في إرساء الثقافة التنظيمية وحدة الخضراء في المؤسسة –دراسة حالة المؤسسة الوطنية للدهن سوق أهراس - - خولة بن غالية; شيماء براكتية (My University, 2021)
This study aimed to show the correlation and influence between the requirements of environmental total quality management and green organizational culture. _This study contained two parts, the first part dealt with the theoretical side in which the variables of the study were dissected, the requirements of environmental total quality management as an independent variable, and the green organizational culture as dependent variables. As for the second part, it was devoted to the field study that took place in the National Institute of Paints ENAP, Ahras Market Unit, where the two researchers relied mainly on distributing a questionnaire to a sample of 40 individuals, and 33 forms were retrieved capable of statistical analysis, with an estimated rate of: 82.5%. _After the analysis process that was based on the statistical program spss, this study came to the following: _There is a clear perception among the respondents about the application of quality management _ There is a clear perception among the respondents about the application of total environmental quality management and green organizational culture in the institution under study - The study showed that there is a positive correlation between the requirements of environmental total quality management and green organizational culture. - The study also showed that there is an influence relationship between the requirements of environmental total quality management and green organizational culture, and the most important influence relationship was between customer focus and green organizational culture .................................................... هدفت هذه الدراسة إلى بيان العلاقة والتأثير بين المتطلبات البيئية الكلية إدارة الجودة والثقافة التنظيمية الخضراء. _احتوت هذه الدراسة على قسمين، تناول الجزء الأول الجانب النظري الذي تناولت فيه متغيرات وقد تناولت الدراسة متطلبات إدارة الجودة البيئية الشاملة بشكل مستقل المتغير، والثقافة التنظيمية الخضراء كمتغيرات تابعة. أما الجزء الثاني فقد خصص ل الدراسة الميدانية التي تمت في المعهد الوطني للدهانات وحدة سوق أهراس حيث تم واعتمد الباحثون بشكل رئيسي على توزيع استبانة على عينة مكونة من 40 فردا، وتم توزيع 33 استمارة مسترجعة قادرة على التحليل الإحصائي، بنسبة تقديرية: 82.5 _بعد عملية التحليل التي اعتمدت على البرنامج الإحصائي توصلت هذه الدراسة إلى ما يلي: _يوجد تصور واضح لدى أفراد العينة حول تطبيق إدارة الجودة _ يوجد تصور واضح لدى أفراد العينة حول تطبيق الجودة البيئية الشاملة الإدارة والثقافة التنظيمية الخضراء في المؤسسة قيد الدراسة - أظهرت الدراسة أن هناك علاقة ارتباطية موجبة بين المتطلبات البيئية الكلية إدارة الجودة والثقافة التنظيمية الخضراء. - كما أظهرت الدراسة أن هناك علاقة تأثيرية بين المتطلبات البيئية إدارة الجودة الشاملة والثقافة التنظيمية الخضراء، وكانت العلاقة التأثيرية الأكثر أهمية بين التركيز على العملاء والثقافة التنظيمية الخضراء